The millennial employees in Central Jakarta: How do they commit to the company? - Erny Hutabarat; Aziza Hasna (President University, 2022)
Generation Y, also known as Millennials, is a strong dominant in the workforce and becomes one of the key holders in the industry's success and economy. Unfortunately, the highest turnover rate is coming from this generation with their behavior of working short tenure and how fast they are changing jobs worries many organizations as this ceases the organization’s growth, productivity, and performance. This research aimed to determine the relationship between career development, compensation, and work environment on millennials' turnover intention. Quantitative method is conducted and surveyed with 172 Central Jakarta's millennial employees who had worked at least 1 year. Partial Least Square PLS-SEM, SPSS, and pre-survey interview analysis were used to analyze the data. The result showed that career development and compensation have a significant negative influence on turnover intention. However, work environment has not significant influence on millennials employees’ turnover intention in Central Jakarta.